JØDER, ARABERE OG ARABISKE JØDER: Udviklinger inden for nationalitetsforståelse i Israel - Feldman, Maia (Tidsskriftet Antropologi, 1998)
Maia Feldman: Jews, Arabs, and Arab Jews. Developments within the Concept of Nationality in Israel The social development in Israel since the 1950s is an example of ho w groups of people - in this case Jews of respectively European and Middle Eastem origin - can experience marked cultural and biological differences between one another, and how in a relatively short period of time, a powerful sense of sameness can emerge. This process is reflected in the Israeli concept of “nationality” and has implied an essentialized meaning of Jewishness and by implication of “Arabs”. This article examines how the perception of “Jews” and “Arabs” as two essentially different “kinds” is expressed, and in some cases opposed, by Israeli Jews of Middle Eastem/Arab origins.